Associated bacterial and fungal infections in burn wounds: Common factors, distribution in etiology, age groups, bacterial and fungal strands - Evaluation of a single burn center experience of 20 years - Christian Weinand (Elsevier, 2024)
Introduction: Burn intensive care unit (BICU) patients suffer from reduced immunological competence. Often bacterial and fungal infections occur as single or associated infection of the burn site. However, common factors in associated infections are discussed controversially. In this study we evaluated factors common in associated occurrence of bacterial and fungal infection in the burn population. Patients and methods: In total 213 patients, admitted to the ICU of Cologne Merheim Clinical Center between 1988 and 2011, with associated infections were included in this study. Exclusion criteria were no bacterial, or no fungal infection, or incomplete data. Data evaluated were sex, age, type of burn injury, total body surface area (TBSA), abbreviated burn severity index (ABSI) score, 3rd degree burn, inhalation injury, length of BICU stay, antibiotic therapy, bacterial strand, fungal strand, incidence of bacteria and fungus infection, single or associated occurrence and bacteria species associated with fungus species. Statistical analysis comprised of univariate, Chi-square and Fischer Exact test, multivariate analysis, positive and negative predictive value, logistic regression analysis with the Nagelkerke, Cox/ Snell R-square. Results: 196 patients were included into the study, 147 male and 49 female. Total mean age was 47 years, in the fire burn group 47 years, in scalding 53 years, in electrical burn 29 years and in chemical burn 62 years. 123 male and 45 female were combusted, 15 male and 3 female scalded, 9 male had an electrical burn and 1 female a chemical burn. The mean TBSA in fire burns was 41 %, in scalding 42 %, in electrical burns 46 %, and in chemical burn 16 %. The mean ABSI in fire burn and scalding was 9, in electrical burn 8 and in chemical burn 7. The 3rd degree burns were 16 % in fire burn and 13 % in scalding and electrical burn and 0 % in chemical burn. The length of BICU stay was 49 days for fire burn, 47 days for scalding, 58 days in electrical burn and 21 days in chemical burn patients.The gram-positive bacterial strands most often found were Staphylococcus strands, gram negative Pseudomonas and Acinetobacter strands. Candida albicans was the most often present fungal strand. There was no difference in incidence between gram positive and gram-negative bacteria. In patients suffering from fire burns the most common bacteria were Staphylococcus and Pseudomonas, in scalding Acinetobacter, and in chemical burns Staphylococcus. In electrical burns no predominant bacterial strand was found. The associated occurrence of Staphylococcus and Candida albicans and Pseudomonas and Candida albicans was predominant. In patients with fire burn, 48% showed an associated infection, in scalding 21%, in electrical burn 33% and in chemical burn 100%.Combusted patients had the highest incidence of associated infection in age group 80-89 years, in scalding 40-49, 50-59 and 70-79 years, in electrical burn 20-29 years and in chemical burn 60-69 years. Most common factors of associated infections were higher age, high TBSA with 3rd degree burns and bacterial infections. Interestingly inhalation injury was highly inversely correlated to associated infection. Conclusion: The associated occurrence of bacterial and fungal wound infection is highest in burn patients with infections with Staphylococcus or Pseudomonas, the incidence is mainly found in fire burn and electrical burns. The use of oxygen in inhalation injury might prevent associated bacterial and fungal infections.